Real-world Case Series of iStent or iStent inject Trabecular Micro-Bypass Stents Combined with Cataract Surgery - Manning, David (Ophthalmol Ther, 2019)
INTRODUCTION: This real-world retrospective case series assessed 12-month effectiveness and safety following implantation of iStent(®) or iStent inject(®) trabecular micro-bypass with cataract surgery. METHODS: Consecutive patients were implanted with either iStent (comprising 1 stent) or iStent inject (comprising 2 stents), together with cataract surgery. Most patients had primary open-angle glaucoma. Effectiveness outcomes through 12 months included intraocular pressure (IOP) and glaucoma medications. Proportional analyses were completed for eyes achieving IOP ≤ 18 mmHg, IOP ≤ 15 mmHg, or IOP reduction ≥ 20% from preoperative; and eyes on 0 medications or ≥ 2 medications. Safety outcomes included adverse events, secondary surgeries, visual acuity, and visual fields. RESULTS: This analysis included 137 eyes (67 iStent, 70 iStent inject) with cataract and mild to moderate glaucoma or ocular hypertension. Over 73% of eyes in both groups had early disease, and ~ 22% had prior glaucoma surgery. At 12 months postoperatively, mean IOP decreased from 18.4 ± 4.2 mmHg to 14.2 ± 2.5 mmHg in iStent eyes (p < 0.0001), and from 20.4 ± 5.6 mmHg to 14.4 ± 2.1 mmHg in iStent inject eyes (p < 0.0001). The IOP reduction was significantly greater for iStent inject eyes than iStent eyes (6.0 mmHg versus 4.2 mmHg reduction, p = 0.034). Both groups had high proportions of patients achieving the 12-month IOP endpoints, although consistently greater proportions reached these endpoints after iStent inject than iStent: 95.7% versus 92.5% had IOP ≤ 18 mmHg, respectively; 74.3% versus 71.6% had IOP ≤ 15 mmHg, respectively; and 68.6% versus 62.7% had IOP reduction ≥ 20% from baseline, respectively. Mean medication burden at 12 months decreased from 1.8 ± 0.7 to 0.3 ± 0.5 medications in iStent eyes (84.0% reduction, p < 0.0001), and from 1.3 ± 0.9 to 0.1 ± 0.3 medications in iStent inject eyes (94.7% reduction, p < 0.0001). Significantly more iStent inject eyes were medication-free at 12 months than iStent eyes (92.9% versus 76.1% medication-free, respectively; p = 0.0068). Favorable safety included few adverse events, no secondary glaucoma surgeries, and stable visual acuity and visual fields in both groups. CONCLUSION: Significant and safe IOP and medication reductions were achieved through 12 months after iStent or iStent inject implantation with cataract surgery. iStent inject eyes had greater absolute IOP reduction and more eyes medication-free versus iStent eyes. FUNDING: Glaukos Corporation.